COVID-19-related restrictions and quarantine COVID-19: Effects on cardiovascular and yo-yo test performance in professional soccer players - de Albuquerque Freire, L.; Tannure, M.; Sampaio, M.; Slimani, M.; Znazen, H.; Bragazzi, N. L.; Aedo-Muñoz, E.; Sobarzo Soto, D. A.; Brito, C. J.; Miarka, B. (Frontiers in Psychology, 2020)
The present study aimed to verify the quarantine`s effects during a serious viral outbreak on the cardiovascular and performance associated with the Yo-Yo test in a sample of professional soccer players. 20 high-level soccer players (n = 20; age: 26 ± 4 years-old; weight: 76.85 ± 6.7 kg; height: 179 ± 6 cm) participated in this study. The intermittent Yo-Yo test was performed pre- and post- COVID-19 quarantine in a random order. During each test, the soccer players` running performance outcomes were monitored using a portable 5-Hz GPS with a 100 Hz accelerometer and a paired t-test was conducted at a p-value of = 0.05. The main results demonstrated significant differences between pre- versus post-COVID-19 quarantine in the following variables: relative distance (161.7 ± 5.9 > 141.1 ± 33.8 m/min), maximal speed (18.7 ± 0.9 > 18.2 ± 0.6 km/h), acceleration (60 ± 20 frequency > 52 ± 16 frequency), deceleration (34 ± 13 frequency > 27 ± 6 frequency), sprints > 19 km/h [0.8 (0.2;3)% >0.5 (0;0.5)%], and in high intensity running distance [16.48 (2.68;41.64)m > 0.827 (0.164;3.0)m]. We concluded that COVID-19-related restrictions and quarantine COVID-19 demonstrated adverse effects on professional soccer players` Yo-Yo tests performance.